Стрессоустойчивость – гендерный аспект - Кузнецов, Р. А. (ХНУРЕ, 2020)
Unfortunately, stress has become an integral part of our lives. Gender stereotypes have a big impact on people's behavior and stress tolerance. The work focuses on the most important parts and gives a practical set of recommendations for the cases that happen to each of us.
Keywords: философия; стрессоустойчивость